Structural Neuroimaging in Substance-Induced Psychosis - Atmaca, Murad; Tabara, Muhammed Fatih (Springer, 2026)
Purpose of Review This review evaluates structural neuroimaging research on substance-related psychosis to determine if these conditions share common neurobiological pathways with primary psychotic disorders, such as schizophrenia, or exhibit unique signatures. Recent Findings Research indicates that methamphetamine, cannabis, and cocaine induce significant structural changes, including cortical thinning and grey matter loss. Methamphetamine-induced psychosis is associated with frontal lobe reduc-tions and smaller hippocampal and amygdalar volumes. Cannabis use is linked to alterations in the cingulate cortex and cer-ebellar networks, particularly when use begins early in life. While many neuroimaging patterns overlap with schizophrenia substance-specific variations exist. For instance, methamphetamine users show more pronounced amygdalar reduction than those with primary psychosis. Generally, structural deficits are more severe and widespread in schizophrenia than in purely substance-induced cases. Summary Substance-induced psychoses exhibit neuroanatomical signatures largely similar to primary psychoses, though distinct regional variations suggest partially divergent mechanisms. Future longitudinal and multimodal research is essential to identify definitive biomarkers for clinical differentiation
Keywords: Substance-Induced Psychosis; Neuroimaging; Structural Mri; Cannabis; Methamphetamine